A swiftly tilting planet eaudiobook - L'Engle, Madeleine (Time Quintet, 2012)
In this companion volume to A Wrinkle In  Time (Newbery Award winner) and   A Wind In The Door fifteen-year-old  Charles Wallace and the unicorn Gaudior undertake a  perilous journey through time in a desperate  attempt to stop the destruction of the world by the  mad dictator Madog Branzillo. They are not alone in  their quest. Charles Wallace's sister, Meg—grown  and expecting her first child, but still able to  enter her brother's thoughts and emotions by  "kything"—goes with him in  spirit. But in overcoming the challenges, Charles  Wallace must face the ultimate test of his faith and  will, as he is sent within four people from  another time, there to search for a way to avert the  tragedy threatening them all. "L'Engle's  gifts are at their most impressive here." —   Publisher's Weekly